'We want to be seen as partners, not vultures of the world:' perspectives of Canadian stakeholders on migration of international students studying in health professions in Canada. (8th August 2018) - Neiterman, Elena; Atanackovic, Jelena; Covell, Christine; Bourgeault, Ivy Lynn
ABSTRACT: According to UNESCO, the number of international students worldwide will reach 7 million by 2020. This pilot study examined the Canadian stakeholders' perspectives on migration and integration of international students enrolled in health professions' studies in Canada. Qualitative interviews with representatives of migration, education, and health sector communities revealed that international students are a desirable group of immigrants, but their 'non-immigrant' status creates a unique set of disadvantages for those intending to stay in Canada. In conclusion, we discuss the role of institutional policy in migration and professional integration of international students in Canada and globally.